2015
DOI: 10.1159/000430282
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke and Estrogen Signaling in Human Airway Smooth Muscle

Abstract: Aims: Cigarette smoke (CS) in active smokers and second-hand smoke exposure exacerbate respiratory disorders such as asthma and chronic bronchitis. While women are known to experience a more asthmatic response to CS than emphysema in men, there is limited information on the mechanisms of CS-induced airway dysfunction. We hypothesize that CS interferes with a normal (protective) bronchodilatory role of estrogens, thus worsening airway contractility. Methods: We tested effects of cigarette smoke extract (CSE) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 66 publications
1
34
0
Order By: Relevance
“…Two days after transfection, the cells were used for the experiment. As described previously [18], RT–PCR was performed to test the Nox2 mRNA expression. Nox2 primers were as follows: forward primer: ACTTCTTGGGTCAGCACTGG; reverse primer: ATTCCTGTCCAGTTGTCTTCG.…”
Section: Methodsmentioning
confidence: 99%
“…Two days after transfection, the cells were used for the experiment. As described previously [18], RT–PCR was performed to test the Nox2 mRNA expression. Nox2 primers were as follows: forward primer: ACTTCTTGGGTCAGCACTGG; reverse primer: ATTCCTGTCCAGTTGTCTTCG.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have suggested the stimuli for regulation SIRT1 expression in bronchial epithelial cells. It has been reported that exposure to cigarette smoke is an important stimulus for asthma and leads to more asthma symptoms [27]. Pace et al found that stimulation with cigarette smoke extracts decreases the activity and levels of SIRT1 in 16HBE cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear whether sex steroids are detrimental or beneficial in the airway. For example, we have demonstrated an acute bronchodilatory role for estrogen via effects on epithelial cells as well as ASM (Townsend et al, , ; Sathish et al, ). However, progesterone has been shown to increase airway hyperreactivity in sensitized male mice (Hellings et al, ), whereas testosterone exhibits bronchodilator effects similar to estrogen (Kouloumenta et al, ; Bordallo et al, ).…”
mentioning
confidence: 91%